Control of polymerization shrinkage and stress in nanogel-modified monomer and composite materials - Moraes, Rafael R. (2011)
OBJECTIVES: This study demonstrates the effects of nano-scale prepolymer particles as additives to model dental monomer and composite formulations. METHODS: Discrete nanogel particles were prepared by solution photopolymerization of isobornyl methacrylate and urethane dimethacrylate in the presence of a chain transfer agent, which also provided a means to attach reactive groups to the prepolymer. Nanogel was added to triethylene glycol dimethacrylate (TEGDMA) in increments between 5 and 40 wt% with resin viscosity, reaction kinetics, shrinkage, mechanical properties, stress and optical properties evaluated. Maximum loading of barium glass filler was determined as a function of nanogel content and composites with varied nanogel content but uniform filler loading were compared in terms of consistency, conversion, shrinkage and mechanical properties. RESULTS: High conversion, high molecular weight internally crosslinked and cyclized nanogel prepolymer was efficiently prepared and redispersed into TEGDMA with an exponential rise in viscosity accompanying nanogel content. Nanogel addition at any level produced no deleterious effects on reaction kinetics, conversion or mechanical properties, as long as reactive nanogels were used. A reduction in polymerization shrinkage and stress was achieved in proportion to nanogel content. Even at high nanogel concentrations, the maximum loading of glass filler was only marginally reduced relative to the control and high strength composite materials with low shrinkage were obtained. SIGNIFICANCE: The use of reactive nanogels offers a versatile platform from which resin and composite handling properties can be adjusted while the polymerization shrinkage and stress development that challenge the adhesive bonding of dental restoratives are controllably reduced.